The acute effect of different stretching methods on sprint performance in taekwondo practitioners - Alemdaroglu, U.; Köklü, Y.; Koz, M. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The purpose of this study was to compare the acute effects of different stretching types on sprint performance in taekwondo practitioners.